Growth of Escherichia coil, Salmonella enterica and Listeria spp., and their inactivation using ultraviolet energy and electrolyzed water, on 'Rocha' fresh-cut pears - Graça, Ana (2019)
The present study aimed at evaluating the growth of Escherichia coil, Salmonella enterica, and Listeria spp. and studying the efficacy of Ultraviolet-C (UV-C) irradiation, acidic electrolyzed (AEW) and neutral electrolyzed (NEW) waters in the reduction of these bacteria on 'Rocha' pear. Fresh-cut pieces were inoculated and incubated at 4-20 degrees C for 8 days. Inoculated pears were treated with UV-C (2.5-10 kJ/m(2)), AEW, NEW and sodium hypochlorite (SH) and microbiological and quality parameters were evaluated. The three bacteria, inoculated at 6.1-6.2 log cfu/g, grew on the pear at high growth rates at 12 and 20 degrees C reaching populations of 8.1-8.6 log cfu/g, in 24 h. At 8 degrees C the microorganisms increased their populations by at least 1 log cfu/g in three days. At 4 degrees C adaptation phases of less than 24 h for Listeria spp. were measured before exponential growth occurred and the enterobacteria did not grow despite having survived for 8 days. AEW and NEW caused microbial reductions similar to SH, of approximately 1 log cfu/ g, while the best UV-C dose (7.5 kJ/m(2)) of at least 2.4 log cfu/g. Fresh-cut pears were a good substrate for foodborne bacteria emphasizing the importance of preventing contaminations and cross contaminations. The UV-C was more effective than the chemical decontaminations, as it provided superior microbial reductions without greatly affecting the quality of pears. (C) 2017 Elsevier Ltd. All rights reserved.